Prevalence, Clinical Manifestations, Treatment Outcomes, Cost Of Treatment And Health Related Quality Of Life (Hrqol) Of Chronic Pulmonary Aspergillosis (Cpa) In A Tertiary Referral Hospital In Lahore, Pakistan - Akram, Waqas (2023)
Chronic Pulmonary Aspergillosis is a chronic progressive infection that destroys lung tissue in non-immunocompromised patients. There has been a dearth of investigation on the CPA. Therefore, a two-phase retrospective and prospective study was conducted to assess the epidemiology, clinical manifestations, treatment outcomes, risk factors associated with the development, prolonged Length of Stay, mortality, direct cost of treatment, and Health Related Quality of Life of CPA patients attending Gulab Devi Chest Hospital, Lahore, Pakistan. During retrospective phase (2017-2019), a total of 44,028 respiratory patients were reviewed. CPA was observed in 248 (0.56 %) cases. The prevalence of CPA was 563/100,000. A total of 218 CPA patients were included in this phase. The most common phenotype of CPA was Simple Aspergilloma (56.0%) followed by Chronic Cavitary Pulmonary Aspergillosis (31.2%) and Sub Acute Invasive Aspergillosis (12.8%) respectively. The most common symptoms in the CPA patients were cough (95.0%), fatigue (92.7%), sputum production (90.4%), fever (85.8%), hemoptysis (59.6%), and weight loss (34.9%). Tuberculosis (62.8%), Non-Tuberculosis Mycobacteria (30.7%), and Diabetes Mellitus (29.8%) were the most common underlying diseases. After CPA was diagnosed,